Nonlinear impacts of climatic variability on the density dependent regulation of an insect vector of disease - Chaves, Luis F (2011)
Aedes aegypti is one of the most common urban tropical mosquito species and an important vector of dengue, chikungunya, and yellow fever viruses. It is also an organism with a complex life history where larval stages are aquatic and adults are terrestrial. This ontogenetic niche shift could shape the density-dependent regulation of this and other mosquito species, because events that occur during the larval stages impact adult densities. Herein, we present results from simple density-dependent mathematical models fitted using maximum likelihood methods to weekly time series data from Puerto Rico and Thailand. Density-dependent regulation was strong in both populations. Analysis of climatic forcing indicated that populations were more sensitive to climatic variables with low kurtosis, i.e., climatic factors highly variable around the median, rainfall in Puerto Rico, and temperature in Thailand. Changes in environmental variability appear to drive sharp changes in the abundance of mosquitoes. The identification of den sity-independent (i.e., exogenous) variables forcing sharp changes in disease vector populations using the exogenous factors statistical properties, such as kurtosis, could be useful to assess the impacts of changing climate patterns on the transmission of vector-borne diseases.